30. Vendor-Assisted Evaluation of a Learning Management System - Fahrni, Patricia; Rudolph, Jim; De Schutter, Adrienne (International Review of Research in Open and Distributed Learning, 2004)
A product evaluation was conducted of Desire2Learn, an online learning management system gaining popularity in educational institutions. Since an online trial version of the software was not available for evaluation, an inspection meeting with the vendor was arranged. This provided the evaluation team with an opportunity to examine the precautions necessary for ensuring the objectivity of a product evaluation based on vendor-supplied information. The report outlines the team’s use of evaluator-driven enquiry and a triangulated approach to information checking. The Desire2Learn product is assessed as a flexible and useful addition to the range of learning management system options.